Prevalence of psychiatric illnesses after major limb amputation and early recognition and treatment in economically lower income group patients - Ali, Zameer; Khurshid, Lubna; Bhat, Towseef; Bhat, Aejaz A.; Vakil, Suhail M. (International Journal of Research in Orthopaedics, 2018)
Background: There is high prevalence of psychiatric illness after major limb amputation and need for early recognition and treatment should be the goal but often is overlooked. Psychological support by the treating physician and the surgeon can help in adaptation to the disability but unfortunately is often overlooked. Methods: A total of 120 patients were screened for psychiatric disorder using HADS criteria Anxiety was found to be in 38 (32%) patients and depression was found to be in 27 (23%) (Table 1) (Figure 1) 55 patients had no psychiatric illness. Psychiatric illness either depression or anxiety was found to be in 65 patients. Results: In our state which is a zone of conflict between two countries prevalence of anxiety was 32% and depressive symptoms were 23%, respectively. Causative factors associated with high prevalence of psychological symptoms included unmarried young females, lower socioeconomic status, single earning member, lack of social support, unemployment, traumatic amputation. These ﬁndings were conﬁrmed by a signiﬁcant reduction of anxiety and depression scores in patients who received social support, patients with amputation due to disease, and patients with above the knee amputation. Conclusions: Our study showed higher prevalence of psychological symptoms in association with lower socioeconomic status, single earning member, lack of social support, unemployment, traumatic amputation vs amputation secondary to chronic disease. Extensive rehabilitation with the use of an interdisciplinary team approach is one of the most successful ways to return the amputee to the work place. Surgeons should give proper attention to the psychological state of amputees. Because of high prevalence of psychiatric illness after major limb amputation. It is suggested that psychiatric evaluation and adequate rehabilitation should form a part of treatment.